LEVEL BERPIKIR METAKOGNISI MAHASISWA SELAMA PERKULIAHAN ONLINE DI MASA PANDEMI - Mohammad Archi Maulyda; Anton Budiharjo; Muhammad Erfan; R Radha (IKIP Siliwangi, 2020)
The ability to reflect on yourself or think metacognition is very important for students. Because with this ability students can learn to analyze their mistakes or weaknesses to be corrected and developed in the future. During the pandemic, lectures were carried out online, this resulted in a tendency for students to not seriously attend lectures. The absence of direct supervision from lecturers is one of the reasons this can happen. Thus, researchers assume that the level of metacognition of students who carry out lectures online will also decrease. Therefore, the purpose of this study is to analyze the level of student metacognition during online lectures that have been implemented. Researchers used a qualitative descriptive research approach with a survey method. The research subjects were 120 students who had attended online courses at least 8 meetings or 2 months. The results showed that 83 students were at the lowest level of metacognition (Tacit Use). Meanwhile, students who are at the highest metacognition level are 2 students (Reflective Use). Thus, researchers can conclude that the level of student metacognition during online lectures is still very low.